The Mo modified Ce/TiO2 catalyst for simultaneous Hg0 oxidation and NO reduction. Issue 5 (October 2019) - Zhang, Ping; Pan, Wei-guo; Guo, Rui-tang; Zhu, Xin-bo; Liu, Jian; Qin, Ling; She, Xiao-li
Abstract: TiO2 supported CeMo catalyst (CeMo/TiO2 ) were employed for the first time to simultaneously oxidize elemental mercury (Hg 0 ) and reduce nitrogen monoxide (NO) under simulated SCR atmosphere. The combination of molybdenum oxides and cerium oxides exhibits obvious synergy for Hg 0 oxidation and NO reduction. CeMo/TiO2 -0.3 catalyst exhibited an excellent Hg 0 oxidation and NO reduction efficiencies of over 90% at above 250 °C corresponding to gas hourly space velocity (GHSV) of 119, 000 h −1 (NO reduction) and 1, 190, 000 h −1 (Hg 0 oxidation). Brunauer-Emmett-Teller (BET) surface area was not the dominating factor affecting the CeMo/TiO2 performance. Well-dispersion of active species, abundant chemisorbed oxygen and large surface oxygen capacity were responsible for its high catalytic activity. The presence of Hg 0 exhibited a negligible effect on NO reduction. Low-concentration of NO inhibited the Hg 0 oxidation while a relatively high concentration had a promotional effect inversely due to abundant NO2 . NH3 consumed surface oxygen and competed to adsorb with Hg 0 resulting in the deactivation of Hg 0 oxidation while an excellent recovery was observed after simultaneous cutting off NH3 and introduction of O2 . In addition, CeMo/TiO2 -0.3 catalyst also presented an excellent resistance to SO2 and H2 O poisoning and a good stability and recyclability. The possible mechanism for simultaneous NO reduction and Hg 0 oxidation was proposed for CeMo/TiO2 catalysts. Graphical abstract: The process of NO reduction and Hg0 oxidation over Ce-Mo/TiO2 catalyst. Image 1 Highlights: It is the first time that CeMo/TiO2 catalyst was employed for the research of simultaneous Hg 0 oxidation and NO reduction. Low-concentration of NO inhibited the Hg 0 oxidation while a relatively high concentration had a promotional effect. The presence of Hg 0 exhibited a negligible effect on NO reduction. CeMo/TiO2 -0.3 catalyst had an excellent recovery for NH3 inhibition and resistance to SO2 poisoning.